Advancing LEAN methodology adoption in Serbian manufacturing SMEs: empirical insights and a strategic implementation framework - Pavlović, Dragan; Milosavljević, Peđa; Rajić, Milena; Stanković, Zorana; Takači, Aleksandar (Serbian Journal of Management, 2026)
As manufacturing industries become more competitive around the world, Lean methodology must be used to improve operations and keep the market stable. However, small and medium-sized businesses (SMEs), have a hard time fully implementing Lean because they don't have enough resources, and their organizations are stuck in their ways. This research provides an empirical analysis of the level of application of Lean in manufacturing SMEs in the Republic of Serbia. A structured survey was conducted in which 54 manufacturing SMEs took part, in order to determine the level of Lean adoption, the main obstacles in the implementation process and the influence of factors, such as company size, quality management system and product diversification. The Mann-Whitney U, the Kruskal-Wallis, the Chi-square test and a binary logistic regression were used for qualitative analysis. The results show that there is a strong link between ISO 9001 certification and Lean implementation. Larger enterprises are more likely to adopt Lean than smaller ones. The study presents a customized Plan-Do-Check-Act (PDCA) model for the Serbian SMEs, offering an approach to overcoming implementation barriers. Future research should be directed towards extending the analysis to the Western Balkans and comparing the results to support evidence-based industrial policy development.
Keywords: Lean; Small and Medium Enterprises; Lean tools; Production; Survey; Plan-Do-Check-Act